Building Healthy Community Environments: A Public Health Approach. (November 2018) - Koehler, Kirsten; Latshaw, Megan; Matte, Thomas; Kass, Daniel; Frumkin, Howard; Fox, Mary; Hobbs, Benjamin F.; Wills-Karp, Marsha; Burke, Thomas A.
Environmental quality has a profound effect on health and the burden of disease. In the United States, the environment-related burden of disease is increasingly dominated by chronic diseases. At the local level, public health practitioners realize that many policy decisions affecting environmental quality and health transcend the authorities of traditional health department programs. Healthy decisions about the built environment, including housing, transportation, and energy, require broad collaborative efforts. Environmental health professionals have an opportunity to address the shift in public health burden toward chronic diseases and play an important role in the design of healthy communities by bringing data and tools to decision makers. This article provides a guide for community leaders to consider the public health effects of decisions about the built environment. We present a conceptual framework that represents a shift from compartmentalized solutions toward an inclusive systems approach that encourages partnership across disciplines and sectors. We discuss practical tools to assist with environmental decision making, such as Health Impact Assessments, environmental public health tracking, and cumulative risk assessment. We also identify priorities in research, practice, and education to advance the role of public health in decision making to improve health, such as the Health Impact Assessment, as a core competency for environmental health practitioners. We encourage cross-disciplinary communication, research, and education that bring the fields of planning, transportation, and energy in closer collaboration with public health to jointly advance the systems approach to today's environmental challenges.